Growth pattern of Exclusively Breastfed Babies in Urban Affluent of Bangladesh - Huq, MN; Sarwar, KB (TAJ: Journal of Teachers Association, 2009)
To find out the growth in the exclusively breastfed babies of the affluent mothers and to compare the figures with those of the children in the industrialized countries. Fifty-three babies were selected for this cross-sectional study under 6-month of age with prefixed criteria, such as exclusively breastfed and not fed with any formula. Recommended schedule of immunization (EPI) was followed to weigh and measure for supine length. Data were analyzed using SPSS Version 10.0. Place and time of work: During an 11-month time frame (from May 2007 to April 2008) data were collected from Pediatrics Department of Bangladesh Medical College Hospital and the researcher's chamber at Dhanmondi, Dhaka, where applicable. The data of developed countries showed that in first 3-month of age, the children grow in weight 30 gm/day and in length 3.5 cm/month, followed by weight gain of 20 gm/day and linear growth 2 cm/month in next 3-6 months.1 Our babies could be compared to those figures, with 33.54 gm/day in the weight gain and 4.17 cm/month in linear growth in the first 3 months. The average wt. gain during the next 3 months (3-6 months of age) was 22.3 gm/day and linear growth for this period was 2.12 cm/month. Babies in our country can grow optimally in comparison to those in the industrialized countries or even can exceed, if they are exclusively breastfed and brought up in well-off families with high education of the mothers. TAJ 2009; 22(1): 231-234